Methane Measurements from the GISP2 and Siple Dome Ice Cores - Brook, Edward J. (IEDA: US Antarctic Program Data Center, 2009)
This data set contains methane measurements made in trapped air in the Holocene sections of two ice cores: the Siple Dome ice core in Antarctica, and the Greenland Ice Sheet Project 2 (GISP2) ice core in Greenland. The measurements were made at Oregon State University between 2007 and 2009. Measurements were made relative to the NOAA04 methane concentration scale using a working standard internally calibrated to NOAA certified air standards. Concentrations are corrected for gravitational fractionation and solubility effects in the melt-refreeze extraction. Data are available via FTP in Microsoft Excel (.xls) format.